The role of daily autonomous and controlled educational goals in students' academic emotion states: An experience sampling method approach. (February 2018) - Ketonen, Elina E.; Dietrich, Julia; Moeller, Julia; Salmela-Aro, Katariina; Lonka, Kirsti
Abstract: The present study examines antecedents of university students' academic emotions (Pekrun, Goetz, Titz, & Perry, 2002) in the context of self-determination theory (SDT; Deci & Ryan, 1985; 2000), using real-time assessment and intra-individual analyses. We investigated whether daily autonomous and controlled-motivated educational goals predicted students' academic emotions. University students (N = 55) completed smartphone diaries over 14 consecutive days. The two-week intensive longitudinal data were organized in a hierarchical three-level structure, with situations (Level 1) nested within days (Level 2) nested within students (Level 3). Students' goal motivation was assessed in morning questionnaires, and academic emotions in three daytime questionnaires. The results of the multilevel structural equation models showed that setting self-determined autonomous educational goals predicted positive emotions, whereas controlled motivation predicted negative emotions in everyday academic situations, applying both to within-person processes and between-person differences. Both kinds of goal motivation, autonomous and controlled, were associated with determination in students' daily lives. Highlights: University students' academic emotions are more situation driven than day dependent. Daily educational goals predict these emotions both within and between individuals. Autonomously motivated goals are associated with positive emotional experiences. Controlled motivation is associated with more negative emotional experiences. Both autonomous and controlled motivation are related to feeling of determination.